(untitled) (Research, Society and Development, 2022)
Objective: The aim of this study is to assess the influence of COVID-19 quarantine on pain, psycho-emotional aspects, quality of life and sleep of chronic pain patients. Methodology: Individuals with fibromyalgia, migraine and chronic low back pain were included. The survey was carried out through a questionnaire attached to the Forms application, from Google Drive™, with objective questions about painful and emotional aspects. Results: About 70% of the sample reported worsening of pain intensity and 52% showed an increase in the daily frequency of pain during quarantine. More than half of the individuals (58.8%) reported intense anxiety. In addition, half of the sample (47.1%) reported poor quality of life and poor quality of sleep (51.8%). Just over 60% of the sample did not practice physical activity. In regression analysis, lack of physical activity had 335% chance of increasing pain intensity (β: -1.095, OR: 0.335, p = 0.025), of increasing anxiety by 244% (β: -1.412, OR: 0.244, p = 0.013) and 250% of causing insomnia (β: -1.353, OR: 0.250, p = 0.010). Conclusions: The increase in pain and anxiety in individuals with chronic pain during COVID-19 pandemic negatively influenced quality of life and sleep. Physical inactivity during quarantine predisposed to worsening pain and psycho-emotional aspects.